AKUNTABILITAS DALAM PENYUSUNAN RENCANA KERJA SEKOLAH: STUDI KASUS SEKOLAH YANG MENJADI KEWENANGAN PROVINSI JAWA TENGAH - Nugraha , Aswin Kurniawan Galih Satya (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to depict the accountability for preparing school work plans in state secondary and special education units in the Central Java Provincial Government. This research used qualitative approach. This research was conducted at the Education and Culture Service which is located at Jalan Pemuda No. 134, Semarang City. The data source was obtained and collected directly from informants at the Central Java Province Education and Culture Service. The selection of informants was carried out using snowball sampling. Data collection in this research was carried out by participant observation, in-depth interviews and documentation studies. The results of the research show that the implementation of the principle of school planning accountability is quite good, namely by providing information to stakeholders regarding school planning policies, policy targets that have been implemented in accordance with the vision, mission and goals of the school as well as assessment or evaluation of each planning activity carried out as material. consideration and decision making.